Does fossil oil price matter? Market performance of banks in the dual banking system and policy implications - Shaiban, Mohammed Sharaf; Li, Di; Hasanov, Akram Shavkatovich; Seho, Mirzet (Frontiers in Climate, 2025)
This study examines the impact of oil price shocks on the stock performance of 73 listed banks—41 conventional and 32 Islamic—across dual banking systems in net oil-exporting and importing countries. Employing panel fixed-effects and two-stage least squares (2SLS) IV regressions, we address both endogeneity and unobserved heterogeneity. The results indicate that oil price fluctuations have a significant impact on bank stock returns, with a stronger negative effect during oil price declines, particularly those driven by demand-side shocks. Islamic banks are more sensitive to these fluctuations than their conventional counterparts, reflecting greater exposure to oil-dependent macroeconomic environments. Robustness checks confirm the presence of non-linear and asymmetric effects: bank stock returns respond more adversely to falling oil prices than to increases in oil prices. These responses differ systematically across bank types and levels of national oil dependency. Our findings underscore the importance of accounting for oil price risk in bank valuation and performance forecasting. For financial managers and investors, the results underscore the importance of incorporating oil-related risk factors into portfolio management, stress testing, and pricing models. For regulators and policymakers, the evidence supports the adoption of macroprudential tools such as countercyclical capital buffers and sector-specific supervisory frameworks to strengthen banking system resilience, particularly for Islamic banks operating in oil-dependent economies. Additionally, disclosure standards should be enhanced to improve transparency around oil price exposure, enabling better-informed decision-making across all stakeholder-dependent economies.